Intérpretes e notáveis da literatura e da cultura popular do Maranhão - Igor Gastal Grill; Eliana Tavares dos Reis (Ciências Sociais Unisinos)
This article proposes a reflection about the work of construction of “pantheons” and the practices of eternalization of “figures” through the examination of two publications that are configured in “notable galleries”. We analyzed Academic Profiles and Popular Culture Profiles taking into consideration: (i) the social and political position of the agents (biographers and biographiers), defined by the resources on which their “reputation” and their inscriptions are based on cultural and political struggles; (ii) the structuring strategies of the works, observing the selection and hierarchization of the cases, available space, assigned classifications, among others; (iii) and the contents, adjectives, definitions, finally, the representations explained in the pre-texts and laudatory texts. Thereby, the conditioning factors of affirmation, the logics of action and mechanisms of consecration mobilized by agents who constitute as authorized spokespersons are learned, as well as the multiple patterns of notabilization of “interpreters” of the culture and the regional memory in and of Maranhão.